Business Plan And Financial Plan Training For Tourism Business Start-Up, Kampung Sawah Durimanis, Dukuh, Imogiri, Bantul - Yetti Lutiyan Suprapto; Shadrina Hazmi; Bhustanul Arifin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Kampung Sawah Duri Manis is a start-up business in the tourism sector initiated by the residents of Dukuh village, Imogiri sub-district, Bantul district. As a new business, Durimanis faces uncertain conditions and low management experiences, thus a detailed and documented business plan is required. The purpose of this community service is to assist Kampung Sawah Durimanis team management in actualizing a business plan, and a business financial plan for Durimanis, through theoretical and practical training. The output achieved by this community service is increasing the capacity of Kampung Sawah Durimanis team management, namely being able to make business plans and financial plans that are bankable or have a financial profile that meets the requirements for financing by the financial institutions, as well as the realization of Business Plan documents. These achievements mean addinginsights and increasing the competence of Dukuh village residents in managing and developing Kampung Sawah Durimanis Tourism.